2023
DOI: 10.1177/13567667231167885
|View full text |Cite
|
Sign up to set email alerts
|

Family-friendly wine tourism? The challenge of supplying child-inclusive wine terroir experiences

Abstract: Wine tourism, traditionally understood as an activity practised by adults, has been suggested as a tourism form also adequate and interesting for families with children. However, both literature and practice do not consider this segment to the extent it, arguably, may deserve. Many challenges are associated with the creation of wine tourism offerings for children. Even so, wine estates and destinations attract families, not only for their wine-related attributes but also for their rural and cultural appeal. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…, 2016), convenience is the third most relevant driver of a strong VWEint, especially being parents of young children. This result suggests VWEs may help stakeholders in reaching market segments interested in wine who are often excluded from in-presence wine experiences due to parenthood (Malerba et al. , 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2016), convenience is the third most relevant driver of a strong VWEint, especially being parents of young children. This result suggests VWEs may help stakeholders in reaching market segments interested in wine who are often excluded from in-presence wine experiences due to parenthood (Malerba et al. , 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Coherently with past studies on e-commerce (Chaparro-Pel aez et al, 2016), convenience is the third most relevant driver of a strong VWEint, especially being parents of young children. This result suggests VWEs may help stakeholders in reaching market segments interested in wine who are often excluded from in-presence wine experiences due to parenthood (Malerba et al, 2023). Interestingly, findings from Cho et al (2017) identified family togetherness as the largest constraints-based cluster when it comes to traveling to wine regions, although the same group declared strong wine tourism intentions.…”
Section: The Drivers Of Interest In Virtual Wine Experiences (Vweint)mentioning
confidence: 94%
See 1 more Smart Citation